Keanekaragaman dan Peranan Serangga Pengunjung pada Tanaman Kacang Panjang (Vigna sinensis L) di Kecamatan Kerkap Kabupaten Bengkulu Utara Provinsi Bengkulu - Endang Sulaiman; Pariyanto; Apriza Fitriani; Yuni Puspita (Jurusan Biologi Universitas Negeri Makassar, 2022)
This study aims to (1) determine the diversity of insects on long bean (Vigna sinensis L) plants, and (2) determine the role of visitor insects on long bean plants (Vigna sinensis L) in Kerkap District, North Bengkulu Regency. The location of this research consists of 4 villages located in Kerkap District, North Bengkulu Regency. This research was conducted in January-February 2022 with a direct survey to the field, while the sampling of insects by purposive sampling. Based on the results of research that has been carried out on long bean plantations (Vigna sinensis L) in Kerkap District, North Bengkulu Regency, it was found that insects belonging to 6 orders, 16 families and 26 species were; orisanthetrum Sabina, Pantala flavescens, Neorothemis fluctuans, Junonia orithya, Junonia coenia, Neptis hylas, Appias albino, Appias olferna, Leptosia alcesta, Nyctemera coleta, Aulacophora foveicollis, Gryllotalpa orientalis, Valbintusskiellus nigristractomacsus , Xenocatantops humilis, Conocephalus melaenus, Nezara viridula, Acanthocephala terminalis, Bothrogonia addita, Leptocorisa oratorius, Vespa tropica, Delta unguiculatum, Xylocopa pubescens. The roles of visitor insects include pollinators, predators, fifophagus and insect pests. The diversity index of visitor insects obtained from 4 villages in Kerkap District was categorized as moderate, namely (H') = 1.084. The results of measurements of ecological factors in long bean plantations (Vigna sinensis L) ranged from 28ºC-37ºC, air humidity ranged from 46 %-69% and light intensity ranged from 1105 Lux-2846 Lux.